비용 효율이 높은 24kV급 고압배전반 개발을 위한 Bus Bar 사이즈에 따른 전·자기 손실 특성 분석 - 홍종기(Jonggi Hong); 허정일(Jeong Il Heo); 남석호(Seokho Nam); 강형구(Hyoungku Kang) (전기학회 논문지 P권, 61(4), 2012)
The analysis on the bus bar effect is conducted to develop a cost effective 24kV/2,000A switchgear. The temperature enclosures and bus bars could rise due to several heat sources such as eddy current losses and copper losses. Therefore, a study on the characteristics of the electric field intensity and electromagnetic loss according to the bus bar size in a bus bar compartment is essential to design a electrically reliable high voltage switchgear. It is investigated that the electromagnetic influence to the temperature rising and the dielectric stability according to various bus bar sizes by using finite element method(FEM). The electric field intensity and electromagnetic loss according to various bus bar sizes are calculated to design a reliable and a high voltage switchgear. As results, it is found that the electromagnetic loss and the dielectric stability of bus bar could be determined by a bus bar size. It means that a cost effective 24kV/2,000A high voltage switchgear could be developed by selecting the proper size of a bus bar. Also, it is recognized that the electromagnetic characteristics according to various bus bar sizes in order to design an electrically stable high voltage switchgear when the enclosure size is determined as a fixed value. Futhermore, studies on the various nominal voltage class and bus bar sizes will be conducted to develop a cost effective high voltage switchgear.